Pendidikan Politik dan Kewarganegaraan: Membangun Generasi Muda Melek Politik di Era Digital - Yanda, Safril; Mansyur, Alfi; Rezky, Aulia Putri; Maulida, Irham; Setyaningsih, Dista (Nawadeepa: Jurnal Pengabdian Masyarakat, 2024)
Political and civic education plays a strategic role in fostering democratic awareness and encouraging youth participation in national affairs. However barriers such as inadequate political literacy, misinformation, and lack of interest restrict their participation. This study aims to examine the role of political education in enhancing youth participation in democracy. Using a community-based educational approach, the program implemented seminars, policy debates, and digital media training. The findings indicate that interactive learning methods, such as policy simulations and social media campaigns, effectively increase political awareness and critical thinking among students. Participants showed increased interest in political issues and a better understanding of their rights and responsibilities. The integration of digital platforms further facilitated engagement, making political education more accessible and relevant to youth. The study highlights the importance of revitalizing civic education through participatory methods and digital literacy to empower young voters in shaping a more inclusive and democratic society.